PENGEMBANGAN INSTRUMEN TES DIAGNOSTIK MODEL TESTLET SEBAGAI PENDETEKSI KESULITAN BELAJAR PESERTA DIDIK PADA POKOK BAHASAN LARUTAN PENYANGGA - Muna, Ana; M. Noer, Asmadi; Linda, Roza (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The development of instrument diagnostic test as a testlet model for learning difficulties detection on chemistry is a kind of reserach development which is used ADDIE model. The ADDIE model has consisted some stages such as: Analysis, Design, Development, Implementation and Evaluation. Because some limitations, The research stage just until is done until Implementation stage, that use some doing trial in limited subjects used, is trialed at SMAN 12 and the istruments is done validated by some lectures of Pendidikan Kimia-FKIP, UR. The study aims to: (1) develop of instrument diagnostic test as a testlet model for learning difficulties detection on chemistry is a kind on buffer, (2) Know the learning difficulties detection using on chemistry is a kind diagnostic test model testlet instrument, (3) Know the reliability of the problem, the level of difficulty of the problem, and the differentiation of the problem. The results of the research shows that: (1) The diagnostic test instrument of developed testlet model is stated valid from material aspect, construction aspect, and language aspect, (2) students of class XI IPA 2 SMAN 12 Pekanbaru have difficulty studying on indicators 4, 5 and 6 Students of class XI IPA 3 SMAN 12 Pekanbaru have difficulty studying on indicator 2, 4, and 6. (3) reliability matter 0,55; The difficulty level of the item consists of 15 items of easy category, 12 items on medium category, and 13 items on the difficult category; The problem of differentiator of item item consists of 2 items of good category, 2 items about good category, 9 items about enough category, and 27 items about bad category.Key Words : Learning Difficulties, Diagnostic Tests, Testlets, Buffers.